Relative Export Competitiveness in Indonesian and Malaysian Palm Oil Downstream Products - Tandra, Hansen; Suroso, Arif Imam; Syaukat, Yusman; Najib, Mukhamad (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Palm oil is an important commodity between Indonesia and Malaysia with a higher contribution to the national economy. However, the investigation into its competitiveness is still important due to fierce competition in the global world. This study aims to investigate the Relative Export Competitiveness (REC) of palm oil downstream and its determinant factors between Indonesia and Malaysia from 1970 until 2020. This study utilizes REC based on merchandise trade and multiple regression by using several variables influencing its REC. The findings reveal that REC in Indonesia has been greater than that of Malaysia over the past 20 years. Initially, Malaysia had a stronger position in REC than Indonesia, particularly from 1971 to 1997. Our analysis demonstrates that REC in Indonesia is positively influenced by factors such as the palm oil policy, the existence of palm oil organizations, and the official exchange rate. Conversely, GDP per capita and the palm oil policy positively impact Malaysia's REC. However, Foreign Direct Investment (FDI) and the ASEAN Free Trade Agreement (AFTA) have a negative effect on REC in both countries. Based on these results, Indonesia and Malaysia must examine proper palm oil downstream policy to boost competitiveness. Keywords: business analytics, determinant factor, palm oil downstream, relative export competitiveness, trade